The effectiveness of temperature control of thermocyclers in PCR optimization - Elisa A Santos; Roberto M Ichinose; Rosimary T Almeida (BioTechniques, 2019)
This study evaluated the effectiveness of thermocycler temperature control, considering the influence of other determinant factors for the optimization of PCR. The reduction in the number of repeated PCR tests, applied in the diagnosis and prognosis of chronic myeloid leukemia at the National Cancer Institute in Brazil, was used as a measure of effectiveness. This indicator was evaluated using samples obtained before and after the temperature control in the wells of the thermocyclers. There was a reduction of 18.9% in the number of repeated exams in the second sample. A structured interview with laboratory staff indicated that there was no change in the other determinant factors.